How Do International EFL Textbooks Teach Moral Values to Indonesian Primary School Students? - Salma Yonalia; Djatmika Djatmika; Ngadiso Ngadiso (JEELS (Journal of English Education and Linguistics Studies), 2024)
Studies of the representation of moral values in English textbooks in Indonesia have developed in recent years. However, there is still little research that reveals the use of speech acts to represent moral values through sayings presented in elementary school students' textbooks. This research investigates the representation of moral values depicted through sayings in international English textbooks for elementary schools in classes 2 and 6 in Indonesia. By adopting Searle's (1969) speech act theory, this qualitative research explains that the representation of moral values is only found in oral texts. The data were analyzed by applying several steps from Krippendoff (2004). The findings of this research indicate that responsibility and kindness are the dominant moral values depicted in two English language textbooks for elementary schools in Indonesia. This research implies that teachers and textbook writers should provide students with more examples of moral values, especially those related to daily life communication both at school and in the family.